KOMPONEN VOTALIT DANKARAKTERISASI KOMPONEN KUNCI AROMA BUAH ANDALIMAN (Zanthoxylum acanthoodium DC.) [Colatile Aroma Constituents and Potent Odorant of Andaliman (Zanthoxylum acanthoodium DC.) Fruit] - C. Hanny Wijaya; Irene Triyanti Hadiprodjo; Anton Apriyantono (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2001)
Andaliman, a wild spice well known in Northem Sumatera, has a fresh citrusy and warm sweet peppery odor. This research was conducted to analyse pontent odorant from andaliman maceration extract using GC-MS, GC/O and aroma extract dilution analysis (AEDA) method. Monoterpenes were the main constituens among the 24 identified components by GC-MS. Results od AEDA revealed that citronellal and limonene had the greatest impact on the aroma of andaliman with flavour dilution factor 128 and 32. β-myrcene, 2-β-ocimene, linalool, β-citronellol, neral, geraniol, gerabial, geranyl acetate, an unkwown compound, and a sesquiterpene also contributed to andaliman fresh citrusy and warm sweet peppery aroma.